Updated spatial analysis of areas of occurrence of bovine cysticercosis in the state of Espírito Santo, Brazil - Gomes, Júlia Bertoli (2023)
The risk of bovine cysticercosis is mutable over time, since population habits, local infrastructure, and bovine herd size change through the years. Hence, the aim of this study was to update the risk map of bovine cysticercosis occurrence in Espírito Santo State, Brazil, by choosing the following risk factors: inadequate sewer service; bovine population per municipality; risk of flooding; and land use and occupation, examined with a mathematical model using the GIS program ArcGis 10.5. The risk map of occurrence demonstrated that the state is composed of 12.8, 24.5, 36.2 and 26.5% of areas of very high, high, medium, and low risk, respectively. The northern area stood out for areas of very high risk, with the cities of Linhares and São Mateus accounting for 99% of the area with this classification. Of the state’s 78 municipalities, 15 had a portion of their territory with very high risk, 11 had over 50% of the territory with high risk and all except Irupi (100% of low risk) had some percentage of medium risk. These findings demonstrate the areas where actions to prevent bovine cysticercosis should be preferentially conducted.